CHARACTERISTICS OF MOTIVATION IN THE SELLERS’ PROFESSION - N. B. Toxanbaeva; Z. B. Madaliyeva; L. N. Rogaleva; A. E. Tlebaldina (Scientific Journal of Pedagogy and Economics, 2019)
The research target is to reveal peculiarities of sellers motivational profile. The research was carried out in “Kego-S” ltd in Almaty city. There have been sellers and founders of “Kego-S” ltd involved in research. The total volume of choice amounted to fifty people. There have been three men and forty seven women among them. An average age of tested was 33. To research peculiarities of sellers motivational profile we applied the following methodic: Motivation profile of Ricci Martin, Psychological typology of leading roles identification of Meredit Bellbin, Definition of labor motivation type of V.I.Gerchikov, “Constructiveness of Motivation” methodic of O.P.Eliseyev. The recognition gain from other people is leading, i.e. in people around appreciated merits, achievements and various means: from oral gratitude to material encouragement that says about the prevailing factor of non-monetary motivation of the trade personnel. The received arithmetic-mean indicators of sellers role features in a section of Belbin test results correspond to a standard professiogramm of the seller, implementers and diplomats on the role qualities correspond to this professional identity. The seller with the prevailing role of the diplomat, is adjusted on cooperation, a susceptibility, diplomacy and prevention of friction, has a high need for closer contacts with others for establishment of rules and directives of work performance and for a comfortable surrounding situation. As the conclusions drawn by results of research, authors state about need of "actions" system for introduction of not monetary motivation. The main effect reached by means of similar stimulation is an increase of loyality level and interest of employees in the company.